Interleukin-35-Producing CD8α+ Dendritic Cells Acquire a Tolerogenic State and Regulate T Cell Function - Haller, Sergio; Duval, Anaïs; Migliorini, Romain; Stevanin, Mathias; Mack, Vanessa; Acha-Orbea, Hans (Frontiers in Immunology, 2017)
Dendritic cells (DCs) play a central role in shaping immunogenic as well as tolerogenic adaptive immune responses and thereby dictate the outcome of adaptive immunity. Here we report the generation of a CD8α+ DC line constitutively secreting the tolerogenic cytokine interleukin (IL-)35. IL-35 secretion led to impaired CD4+ and CD8+ T lymphocyte proliferation and interfered with their function in vitro but also in vivo. IL-35 was furthermore found to induce a tolerogenic phenotype on CD8α+ DCs, characterized by the up-regulation of CD11b, downregulation of MHC class II, a reduced co-stimulatory potential as well as production of the immunomodulatory molecule interleukin-10. Vaccination of mice with IL-35 expressing DCs promoted tumor growth and reduced the severity of autoimmune encephalitis not only in a preventive but also after induction of encephalitogenic T cells. The reduction in EAE severity was significantly more pronounced when antigen pulsed IL-35+ DCs were used. These findings suggest a new, indirect effector mechanism by which IL-35 responding antigen-presenting cells contribute to immune tolerance. Furthermore, IL-35 transfected DCs may be a promising approach for immunotherapy in the context of autoimmune diseases.